2017
DOI: 10.1101/173229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signatures of selection at drug resistance loci inMycobacterium tuberculosis

Abstract: Abstract-2509

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…However, one study showed that an M. tuberculosis strain harboring a deletion in pncA conferring pyrazinamide resistance was estimated to be endemic longer before the use of pyrazinamide for TB treatment [26]. This finding supports the idea that purifying selection on pncA is relatively weak, which would contribute to its exceedingly high diversity and broaden the adaptive paths to resistance [27].…”
Section: Discussionmentioning
confidence: 95%
“…However, one study showed that an M. tuberculosis strain harboring a deletion in pncA conferring pyrazinamide resistance was estimated to be endemic longer before the use of pyrazinamide for TB treatment [26]. This finding supports the idea that purifying selection on pncA is relatively weak, which would contribute to its exceedingly high diversity and broaden the adaptive paths to resistance [27].…”
Section: Discussionmentioning
confidence: 95%
“…Such studies can benefit from an understanding of the selection pressures shaping genetic diversity and the identification of sites under positive selection because often that selection is driven by drug therapy (e.g. Pepperell et al 2013;Zhang et al 2013;Farhat et al 2013;Osório et al 2013;Lee et al 2015;Koch et al 2017;Mortimer et al 2018).…”
Section: Figurementioning
confidence: 99%
“…If some of the identified polymorphisms indeed lead to a modulation of cytokine induction, we would expect signatures of selection acting upon them. Homoplastic positions, those appearing multiple times and independently in the phylogeny, are generally good surrogates of the action of positive selection 17,18 . By comparing the identified polymorphisms to a collection of 4528 strain genomes representative of the global diversity of the MTBC, we found that five SNP positions from our Porto dataset also emerged in unrelated strains in the phylogeny more than one time.…”
mentioning
confidence: 99%